Barriers Impede Upstream Spawning Migration of Flathead Chub. Issue 1 (11th December 2013) - Walters, David M.; Zuellig, Robert E.; Crockett, Harry J.; Bruce, James F.; Lukacs, Paul M.; Fitzpatrick, Ryan M.
Abstract: Many native cyprinids are declining throughout the North American Great Plains. Some of these species require long reaches of contiguous, flowing riverine habitat for drifting eggs or larvae to develop, and their declining populations have been attributed to habitat fragmentation or barriers (e.g., dams, dewatered channels, and reservoirs) that restrict fish movement. Upstream dispersal is also needed to maintain populations of species with passively drifting eggs or larvae, and prior researchers have suggested that these fishes migrate upstream to spawn. To test this hypothesis, we conducted a mark–recapture study of Flathead Chub Platygobio gracilis within a 91‐km reach of continuous riverine habitat in Fountain Creek, Colorado. We measured CPUE, spawning readiness (percent of Flathead Chub expressing milt), and fish movement relative to a channel‐spanning dam. Multiple lines of evidence indicate that Flathead Chub migrate upstream to spawn during summer. The CPUE was much higher at the base of the dam than at downstream sites; the seasonal increases in CPUE at the dam closely tracked seasonal increases in spawning readiness, and marked fish moved upstream as far as 33 km during the spawning run. The upstream migration was effectively blocked by the dam. The CPUE of Flathead Chub was much lower upstream of the OHDD than at downstream sites, and <0.2% of fish marked at the dam were recaptured upstream. This study provides the first direct evidence of spawning migration for Flathead Chub and supports the general hypothesis that barriers limit adult dispersal of these and other plains fishes.